Ultrasound guided catheter placement for TeQuiLa block: a novel techinique for post-operative analgesia for abdominal surgeries - Bhattarai, Prajjwal Raj (Journal of Society of Anesthesiologists of Nepal, 2018)
Ultrasound guided abdominal plane blocks are being considered as effective measure for postoperative analgesia. Among these Quadratus Lumborum Block has been reported to provide adequate analgesia for abdominal surgeries. Placement of catheter for continuous infusion of local in these plane provide long term analgesia for abdominal surgery. More recently, a transmuscular quadratus lumborum block (TeQuiLa Block) was described by Borglum et al and we have tried to use catheter placement and local anesthetic infusion for the same. Journal of Society of Anesthesiologists of Nepal Vol. 4, No.2, 2017, Page: 94-95